صناعة تصفية ( تكرير) النفط الخام في العراق ومدى التزامها بمتطلبات نظم الادارة البيئية(ISO 14001)/دراسة ميدانية في شركة مصافي الشمال/ بيجي (المجلة العراقية للعلوم الاقتصادية, 2018)
This research aims to diagnose the impact of the oil refining industry on the Iraqi environment and measuring the extent of the organization surveyed to the requirements of the environmental management systems, ISO 14001, and also should be noted that the field of research in Baiji refinery company, which is one of the important companies of the oil industry in Iraq. The research identified a problem in several of questions . The most important of them were concerned the extent of the company's commitment to environmental management systems requirements, and what is the impact of the oil refining industry on the Iraqi environment pollution. In order to achieve the goal of the research and answer questions about the problem and hypothese , this research was applied on a community consists of (38) persons from sections of production and the environment. It was relying on the questionnaire as a main tool to collect data and information, and dealt with the use of a set of statistical tools appropriate to the nature of the research, such as the mean, standard deviation, which carried out using the statistical programs (SPSS) on the computer. The results showed no effect of the oil refining industry on the environment and enhanced with data by the surveyed company, as well as provides environmental management systems requirements in the company, on the one hand, and non-availability, of the other.